Financial Management Behavior Analysis in Student of The Department Management UPN “Veteran” Jawa Timur - Mentari Clara Dewanti; Daisy Marthina Rosyanti; Fani Khoirotunnisa (Future Science, 2022)
Financial knowledge is learned by Generation Z students through lectures, seminars, and training activities carried out by campuses and off-campus institutions that are still considered less able to be applied optimally, this is shown through the lack of responsibility for students to apply the knowledge they get in their daily financial behavior. This study tries to examine financial management in Generation Z, namely students majoring in management at the Faculty of Economics and Business UPN